Comprendre et apprendre dans l'interaction. Les séquences d'explication en classe de français langue seconde - Fasel Lauzon, Virginie (Linguistic Insights, 2014)
This book is about the organization of explanation sequences in classes of French as a second language. It provides a description of how these sequences are organized, an inventory of resources mobilized by students to ask and give explanations, as well as a reflection on learning opportunities for students.